PRODUCTION OF SPACE FOR THE PRODUCTIVE AGEING’S ECONOMIC AND SOCIAL BENEFITS - Phengsrakate, Phatcharawadee (Journal of Humanities and Social Sciences Thonburi University, 2019)
Abstract The article on Production of Space for the Productive Ageing for economic and social benefits. Use documentary research methodology. Analyze on the secondary document. The criteria for the selection of documents are 1) the truth, 2) the credibility, 3) the representation and 4) the meaning, which used all 10 documents. The main conclusions are as follows: The key condition for Production of Space for the elderly is that those who are powerful in Product of Space must be potential. The element of being a senior citizen is the ability to be self-reliant, self-reliant and the ability to participate in economic and social activities. The way to Product of Space for the elderly is to: 1) Collaborate and create an aging network to create bargaining power to create a new image that the elderly are socially and economically beneficial. They also have the power to negotiate for government funding. 2) Putting power relations closer to the state. The goal is to create space in accordance with the development or policy of the state to create mutual benefits. Keywords: Production of Space, Ageing, economic benefits, social benefits